PTPN2 and Leukopenia in Individuals With Normal TPMT and NUDT15 Metabolizer Status Taking Azathioprine - Laura L. Daniel; Puran Nepal; Jacy Zanussi; Alyson L. Dickson; Peter Straub; Tyne W. Miller‐Fleming; Wei‐Qi Wei; Adriana M. Hung; Nancy J. Cox; Vivian K. Kawai; Jonathan D. Mosley; Charles Michael Stein; et al. (Clinical and Translational Science)
ABSTRACT Leukopenia is a common dose‐dependent side effect of azathioprine, often leading to drug discontinuation. Variants in TPMT and NUDT15 are associated with azathioprine‐induced leukopenia but only explain 25% of cases. Thus, we aimed to identify novel genetic risk factors among TPMT and NUDT15 normal metabolizers through a genome‐wide association study (GWAS). Using BioVU, Vanderbilt's electronic health record linked to genetic data, we assembled a discovery cohort of new users of azathioprine. The analysis was conducted in 1184 new users of azathioprine who had no history of prior thiopurine use or an organ transplant. A replication cohort of 521 patients was derived from All of Us, an NIH‐funded project that links healthcare data and genetics. The GWAS was adjusted for sex, age, indication (inflammatory bowel disease, systemic lupus erythematosus, other autoimmune condition, or unknown), concurrent use of xanthine oxidase inhibitors (allopurinol or febuxostat) or immunosuppressants, prior TPMT or NUDT15 testing, and 10 principal components of ancestry. In BioVU, 65% of patients were female with a median age of 44 [IQR: 30, 57] and 125 patients developed leukopenia. In All of Us, 69% were female with a median age of 51 [36, 61], and 44 patients developed leukopenia. An intronic variant in PTPN2, rs11664064, reached genome‐wide significance in BioVU (OR = 3.61; p = 1.96E‐8) and replicated in All of Us (OR = 2.42, p = 0.039). Our finding suggests an association between rs11664064 in PTPN2 and azathioprine‐induced leukopenia. PTPN2 plays a role in immune cell development and differentiation, providing a plausible mechanism for this association.